The writing culture of ordinary people in Europe, c. 1860-1920 - Lyons, Martyn 1946- (Cambridge University Press, 2013)
As war and mass emigration across oceans increased the distances between ordinary people in the late nineteenth and early twentieth centuries, many of them, previously barely literate and unaccustomed to writing, began to communicate on paper. This fascinating account explores this surge of ordinary writing, how people met the new challenges of literacy and the importance of scribal culture to the history of individual experience in modern Europe. Focusing on correspondence and other writing genres produced by French and Italian soldiers in the trenches in the First World War, as well as Spanish emigrants to the Americas, the book reveals how these writings were influenced by dialect and oral speech and were oblivious to the rules of grammar, spelling and punctuation. Through their sometimes moving stories, we gain an insight into the importance to ordinary peasants of family, village and nation at a time of rapid social and cultural change